Prevalence of vitamin D deficiency in urban south Indians with different grades of glucose tolerance. Issue 2 (26th March 2020) - Jayashri, Ramamoorthy; Venkatesan, Ulagamathesan; Shanthirani, Coimbatore S.; Deepa, Mohan; Anjana, Ranjit Mohan; Mohan, Viswanathan; Pradeepa, Rajendra
Abstract: The present study assessed the prevalence of vitamin D deficiency in an urban south Indian population in individuals with different grades of glucose tolerance. A total of 1500 individuals (900 normal glucose tolerance (NGT), 300 prediabetes and 300 with type 2 diabetes mellitus (T2DM)) who were not on vitamin D supplementation were randomly selected from the Chennai Urban Rural Epidemiological Study follow-up study. Anthropometric, clinical examination and biochemical investigations (25-hydroxyvitamin D (25(OH)D), insulin, glycated Hb (HbA1c) and serum lipids) were measured. Vitamin D deficiency was defined as serum 25(OH)D < 20·0 ng/ml, insufficiency as 20–29·9 ng/ml and sufficiency as ≥30 ng/ml. Of the 1500 individuals studied, 45 % were males and the mean age was 46 (sd 12) years. Vitamin D levels lowered with increasing degrees of glucose tolerance (NGT: 21 (sd 11); prediabetes: 19 (sd 10); T2DM: 18 (sd 11) ng/ml, P < 0·001). The overall prevalence of vitamin D deficiency was 55 % and was significantly higher among individuals with T2DM (63 %) followed by prediabetes (58 %) and NGT (51 %) ( P for trend < 0·001). Women had 1·6 times the risk of vitamin D deficiency compared with men (unadjusted OR 1·6 (95 % CI 1·3, 2·0) and adjusted OR 1·6 (95 % CI 1·2, 1·9)). However, there was no increasing trend observed with increasing age. The prevalence of abdominal obesity (66 v . 49 %), generalised obesity (80 v . 64 %), the metabolic syndrome (45 v . 37 %) and insulin resistance (38 v . 27 %) was significantly higher in those with vitamin D deficiency compared with those without. This study shows that vitamin D deficiency is highly prevalent in this urban south Indian population and was higher among individuals with T2DM and prediabetes compared with those with NGT.